Critical Roles for Lipomannan and Lipoarabinomannan in Cell Wall Integrity of Mycobacteria and Pathogenesis of Tuberculosis - Fukuda, Takeshi; Matsumura, Takayuki; Ato, Manabu; Hamasaki, Maho; Nishiuchi, Yukiko; Murakami, Yoshiko; Maeda, Yusuke; Yoshimori, Tamotsu; Matsumoto, Sohkichi; Kobayashi, Kazuo; Kinoshita, Taroh; Morita, Yasu S. (mBio, 2013)
Lipomannan (LM) and lipoarabinomannan (LAM) are mycobacterial glycolipids containing a long mannose polymer. While they are implicated in immune modulations, the significance of LM and LAM as structural components of the mycobacterial cell wall remains unknown. We have previously reported that a branch-forming mannosyltransferase plays a critical role in controlling the sizes of LM and LAM and that deletion or overexpression of this enzyme results in gross changes in LM/LAM structures. Here, we show that such changes in LM/LAM structures have a significant impact on the cell wall integrity of mycobacteria. In Mycobacterium smegmatis , structural defects in LM and LAM resulted in loss of acid-fast staining, increased sensitivity to β-lactam antibiotics, and faster killing by THP-1 macrophages. Furthermore, equivalent Mycobacterium tuberculosis mutants became more sensitive to β-lactams, and one mutant showed attenuated virulence in mice. Our results revealed previously unknown structural roles for LM and LAM and further demonstrated that they are important for the pathogenesis of tuberculosis. IMPORTANCE Tuberculosis (TB) is a global burden, affecting millions of people worldwide. Mycobacterium tuberculosis is a causative agent of TB, and understanding the biology of M. tuberculosis is essential for tackling this devastating disease. The cell wall of M. tuberculosis is highly impermeable and plays a protective role in establishing infection. Among the cell wall components, LM and LAM are major glycolipids found in all Mycobacterium species, show various immunomodulatory activities, and have been thought to play roles in TB pathogenesis. However, the roles of LM and LAM as integral parts of the cell wall structure have not been elucidated. Here we show that LM and LAM play critical roles in the integrity of mycobacterial cell wall and the pathogenesis of TB. These findings will now allow us to seek the possibility that the LM/LAM biosynthetic pathway is a chemotherapeutic target. Tuberculosis (TB) is a global burden, affecting millions of people worldwide. Mycobacterium tuberculosis is a causative agent of TB, and understanding the biology of M. tuberculosis is essential for tackling this devastating disease. The cell wall of M. tuberculosis is highly impermeable and plays a protective role in establishing infection. Among the cell wall components, LM and LAM are major glycolipids found in all Mycobacterium species, show various immunomodulatory activities, and have been thought to play roles in TB pathogenesis. However, the roles of LM and LAM as integral parts of the cell wall structure have not been elucidated. Here we show that LM and LAM play critical roles in the integrity of mycobacterial cell wall and the pathogenesis of TB. These findings will now allow us to seek the possibility that the LM/LAM biosynthetic pathway is a chemotherapeutic target.